2016
DOI: 10.1002/qj.2700
|View full text |Cite
|
Sign up to set email alerts
|

A seamless weather–climate multi‐model intercomparison on the representation of a high impact weather event in the western Mediterranean: HyMeX IOP12

Abstract: High Impact Weather (HIW), particularly Heavy Precipitation Events (HPE), are common phenomena affecting the western Mediterranean (WMED) especially in the autumn period. Understanding and evaluating the capability to adequately represent such events in model simulations is one of the main goals of the Hydrological cycle in the Mediterranean Experiment (HyMeX) and the main motivation of this investigation. In order to gain a better knowledge of the model representation of HPE and related processes we perform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 86 publications
(109 reference statements)
3
37
0
Order By: Relevance
“…The consequence of spatial averaging effect is consistent with Chen and Knutson [] and Khodayar et al [] and is illustrated in Figures a and d which displays the curve drawn from the in situ measurements corrected using the ensemble mean ratio of spatially averaged to local precipitation extremes of Figure . The magenta and green curves mimic the expected SAFRAN and WRF scaling, respectively.…”
Section: Scaling Of Precipitation Extremes With Temperaturesupporting
confidence: 87%
“…The consequence of spatial averaging effect is consistent with Chen and Knutson [] and Khodayar et al [] and is illustrated in Figures a and d which displays the curve drawn from the in situ measurements corrected using the ensemble mean ratio of spatially averaged to local precipitation extremes of Figure . The magenta and green curves mimic the expected SAFRAN and WRF scaling, respectively.…”
Section: Scaling Of Precipitation Extremes With Temperaturesupporting
confidence: 87%
“…Concerning the role of model resolution in regards to the representation of hpes, studies by Déqué and Somot (2008), Torma et al (2015), Fantini et al (2018), Ruti et al (2016) and Prein et al (2016) proved the added value of a horizontal resolution of 12.5 km rcms (Regional Climate Model) with respect to a horizontal resolution of 50 km rcms. In Richard et al (2007) and Khodayar et al (2016), the authors showed that by using a set of explicit convection models at a horizontal resolution of 2 km, the simulated extreme precipitation for some hpe cases was closer to the observations than were the hydrostatic models with a coarser resolution. Berthou et al (2018) showed that when it came to daily precipitation, at a resolution of 12.5 km, two rcms behaved differently concerning the representation of high precipitation events in the Gard in September 2002 whereas their Convective Permitting Regional Climate Model (cprcms) counterpart converged for a better representation.…”
Section: Introductionmentioning
confidence: 97%
“…Although the relevance of the vertical distribution of moisture and related changes for the occurrence of HPSs was already pointed out in the region in Khodayar et al . (), the relationship with the severity of the event and the build‐up time has not been previously discussed. Therefore, further analysis regarding these characteristics will be necessary to assess the generality of our results.…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on a complex single IOP; therefore, it would be of interest to extend the investigation to a large number of events, including other types of convective situations. Although the relevance of the vertical distribution of moisture and related changes for the occurrence of HPSs was already pointed out in the region in Khodayar et al (2016a), the relationship with the severity of the event and the build-up time has not been previously discussed. Therefore, further analysis regarding these characteristics will be necessary to assess the generality of our results.…”
Section: Discussionmentioning
confidence: 99%